Injuries and symptoms in women street runners (Research, Society and Development, 2022)
Objective: To verify the occurrence of injuries and the perception of symptoms in women street runners. Methods: The sample was composed by 60 running women with mean age of 41±10 years. The participants voluntarily answered a form containing questions related to the objectives of the present study by means of an interview. A descriptive analysis was carried out, presented as absolute frequency, relative frequency and mean. Results: It was evidenced that 24 volunteers informed the history of injuries and 24 interviewees reported the perception of symptoms, but not always corresponding to the same women. Fortyone injuries and 35 symptoms were reported. The main places of involvement were the knee (29%), the front of the leg (22%), and the back of the leg (15%). The most frequent types of injuries were: shin splints (17%), strains (12%), and tendonitis (12%). The most frequent symptom was pain, and the most commonly affected symptomatic site was the knee. Conclusion: We conclude that the most frequent injuries in women street runners occur in the knee and the anterior and posterior regions of the leg, and the types of injuries reported were cannellini, stretching and tendinitis. As for the symptoms, pain was the main complaint, and the knee was the most affected site in women street runners.